PALAEOTECTONIC AND PALAEOGEOGRAPHIC EVOLUTION OF THE WESTERN TETHYS AND PERITETHYAN DOMAIN (IGCP PROJECT 369) - Stampfli G.M.; Borel G.D.; Cavazza W.; Mosar J.; Ziegler P.A. (My University, 2001)
Project No. 369 ("Comparative Evolution of PeriTethyan Rift Basins") of the International Geological Correlation Program produced a new palaeotectonic-palaeogeographic atlas of the western PeriTethyan domain. The atlas contains more than two hundred new maps and documents grouped in nine regional sets (Iberia, Polish Trough, Eastern European and Scythian Platforms, Moesian Platform, Levant, Arabian Platform, Northern Africa, NE Africa-NW Arabia, Libya-Pelagian Shelf) plus a set of reconstructions for the whole western Tethys. The area considered in the atlas stretches, from west to east, from the eastern Atlantic shores to the Urals and, from north to south, from the Baltic shield to equatorial Africa; the time span covered extends from the Late Carboniferous to the Present. The dataset, resulting from an extensive cooperation between industrial and academic sources, is accessible interactively on a CD-ROM (Stampfli et al., 2001a) and includes legend, timetable, short explanatory notes, full references and additional supporting data. This dataset provides information on the development of the Tethyan realm in space and time. In particular, the relation between the Variscan and Cimmerian cycles in the Mediterranean realm is illustrated by numerous palaeogeographic and palaeotectonic maps.
Keywords: Carboniferous; Paleozoic::Carboniferous; Палеозой::Каменноугольная